How can a brief intervention contribute to coping with back pain? A focus group study about participants' experiences. Issue 8 (December 2014) - Ree, Eline; Harris, Anette; Indahl, Aage; Tveito, Torill H.; Malterud, Kirsti
Background: Our aim was to explore how individuals who had participated in a brief back and neck pain intervention perceived connections between the intervention and their subsequent coping. Methods : Three focus group discussions were conducted with a sample of ten employees aged 20–67 years, who had participated in a brief intervention for back and neck pain, perceived the intervention as helpful and had returned or remained at work subsequent to the intervention. Participants were invited to share stories of how the intervention had made a positive difference to their work situation and everyday life and helped them cope with their complaints. Systematic text condensation was used for analysis. Results : Analysis revealed several aspects of how the participants considered the intervention to be helpful. They emphasized the importance of having the information delivered in a comprehensible way, with the use of practical examples and images of the spine. Discussions revealed the significance of trusting the lecturers and perceiving them as experts. Understanding why they felt the pain and that it was not a sign of serious disease changed the participants' perception of how they could live with the complaints. They told stories of how they had exceeded their previous limits and dared to undertake activities they previously had avoided due to fear. Conclusions : Having confidence in the lecturers and seeing them as experts that delivered the information in a comprehensible way helped participants to cope with their pain and was seen as the most important aspects of the brief back and neck pain intervention.